Nickel(ii)-modified covalent-organic framework film for electrocatalytic oxidation of 5-hydroxymethylfurfural (HMF). Issue 92 (3rd November 2020) - Cai, Meng; Ding, Sha; Gibbons, Bradley; Yang, Xiaozhou; Kessinger, Matthew C.; Morris, Amanda J.
Abstract : Nickel(ii )-modified covalent-organic framework (COF) film exhibited electrocatalytic oxidation of 5-hydroxymethylfurfural (HMF) with ∼96% conversion. Abstract : Electrochemical oxidation of 5-hydroxymethylfurfural (HMF) is a promising synthetic route for 2, 5-furandicarboxylic acid (FDCA) production. Here, we prepared a nickel(ii )-modified covalent-organic framework (COF) film TpBpy-Ni@FTO for HMF electrooxidation. With a high conversion of HMF (96%), TpBpy-Ni@FTO afforded a 58% FDCA yield. This work underlines the great potential of COF-based materials in electrocatalysis.